The Origin of Intuitionistic Propositional Calculus and Glivenko’s Theorem - Urbańczyk, Piotr (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2014)
Among the non-classical logics, the intuitionistic one stands out in many ways. First of all, because of its properties, it is grateful subject of formal analysis. Moreover, there is small, but very significant group of mathematicians and philosophers who claim that intuitionistic logic captures the reasoning utilized in mathematics better than classical one. This article reveals the origins of intuitionistic propositional calculus – it was an outcome of formalization of certain ideas about foundations of mathematics. A large part of the article is devoted to Glivenko’s Theorem – somewhat forgotten, but extremely interesting formal result regarding the relationship between the two logical calculi: classical and intuitionistic propositional logic.